Screening of zero valent mono/bimetallic catalysts and recommendation of Raney Ni (without reducing agent) for dechlorination of 4-chlorophenol - Raut, Sandesh S.; Shetty, Rohit; Raju, Nikhi Maria; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2020)
Chlorophenol (CP) is considered as environmentally hazardous material due to its acute toxicity, persistent nature and strong bioaccumulation. The dechlorination of 4-CP was investigated by using various catalysts such as bimetallic (Fe-0/Cu-0, Al-0/Fe-0), Pd/C, Raney Ni and Fe-0 at room temperature. Among the catalysts studied, Raney Ni proved to be very economical and efficient catalyst that worked without the use of an external reducing agent. The dechlorination of 4-CP by Raney Ni was therefore further explored. Complete dechlorination of 4-CP (30 mg L-1) was achieved in 6 hat an optimum Raney Ni catalyst loading of 3 g L-1. The effect of triethylamine (TEA) and tripropylamine (TPA) was also investigated and it was observed that 100% dechlorination is possible in presence of 45 mg L-1 of TEA. The kinetics of dechlorination of 4-CP was investigated and found to be first order with a rate constant of 0.017 min(-1) at 50 degrees C, and it enhances to 0.109 min(-1) with addition of TEA. In the absence of a reducing agent, acidic to neutral pH favors dechlorination of 4-CP. The final product of dechlorination was estimated to be phenol by performing HPLC, LCMS and NMR analysis. Based on the results, a probable dechlorination mechanism of 4-CP is also proposed. It can be concluded that the catalytic hydrodechlorination is an effective and economical technique for dechlorination of 4-CP and it has a potential for the dechlorination of other toxic derivatives of chlorinated aromatics. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 4-Chlorophenol; Cl- scavenger; Hydrodechlorination; Raney Ni; Recycling of catalyst; Without reducing agent